2023
DOI: 10.1101/2023.08.30.23294816
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-control is associated with health-relevant disparities in buccal DNA-methylation measures of biological aging in older adults

Y.E. Willems,
A. deSteiguer,
P.T. Tanksley
et al.

Abstract: Self-control is a personality dimension that is associated with better physical health and a longer lifespan. Here we examined (1) whether self-control is associated with buccal and saliva DNA-methylation (DNAm) measures of biological aging quantified in children, adolescents, and adults, and (2) whether biological aging measured in buccal DNAm is associated with self-reported health. Following preregistered analyses, we computed two DNAm measures of advanced biological age (PhenoAge and GrimAge Acceleration) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Specifically, child victimization, family and neighborhoodlevel socioeconomic disadvantage in childhood, and belonging to a marginalized racial or ethnic group are associated cross-sectionally with MPSs that index more advanced biological age, a faster pace of aging, and lower cognitive performance in childhood. [14][15][16][17] Together, this research suggests that MPSs might be useful for quantifying, in real time, how early life experiences affect aging-related biology. However, there is currently very little information regarding when aging-related DNAm patterns are most sensitive to environmental change, versus when they are canalized into relatively stable trajectories.…”
Section: Introductionmentioning
confidence: 88%
“…Specifically, child victimization, family and neighborhoodlevel socioeconomic disadvantage in childhood, and belonging to a marginalized racial or ethnic group are associated cross-sectionally with MPSs that index more advanced biological age, a faster pace of aging, and lower cognitive performance in childhood. [14][15][16][17] Together, this research suggests that MPSs might be useful for quantifying, in real time, how early life experiences affect aging-related biology. However, there is currently very little information regarding when aging-related DNAm patterns are most sensitive to environmental change, versus when they are canalized into relatively stable trajectories.…”
Section: Introductionmentioning
confidence: 88%
“…Given previous research that age-related diseases and mortality can be predicted from early life factors, we probed whether MPSs of biological aging and related phenotypes were sensitive to childhood socioeconomic and racial/ethnic marginalization measured in real-time. In the Texas Twin Project, we found children from underserved families to have MPSs indicating advanced biological age, a faster pace of aging, higher chronic inflammation, higher BMI, and lower cognitive health 26,34,46 . Some of these findings have been replicated in buccal samples from the German SOEP-G sample 27 , as well as the Future Families and Child Well-Being Study, where we found socioeconomic contexts at birth relative to concurrent socioeconomic contexts in childhood and adolescence to be most strongly associated with MPS of BMI in childhood and adolescence ( 26,47 ; for review see also 48 ).…”
Section: Quantifying Biological Aging Early In the Life Spanmentioning
confidence: 97%